La néologie dans Le messager popoli: reflet du visage sociopolitique camerounais de 1993 à 2010 - Madiga, Cécile (Ponti/Ponts, 2021)
This contribution, which focuses on the process of linguistic appropriation and the dynamic of French language in Cameroon, aims to demonstrate that the neologisms observed in the newspaper Le Messager Popoli (LMP), establish an emissary-witness of the events having marked the history of the Cameroonian society during the period 1993-2010. The article analyzes a corpus of about forty high-frequency lexical items. It is based on the hypothesis that the use of a new word, either for its form or for its meaning, is never fortuitous and that it can reveal the face of a people or society at one point of his history. The study of neologisms is based on the speech analysis of LMP, but also on the examination of the structure of the lexico-semantic field of the words, in order to appreciate the striking facts of Cameroonian culture or history. By wondering about the journalistic use of these neologisms, then about their durability in LMP, the paper finally reveals a dark portrait of the Cameroonian sociopolitical life.